The crosstalk between p38 and Akt signaling pathways orchestrates EMT by regulating SATB2 expression in NSCLC cells - Hakan Kucuksayan; Hakan Akca (Tumor Biology, 2017)
Epithelial–mesenchymal transition is a crucial event for metastasis and could be mediated by several pathways such as phosphoinositide 3-kinase/Akt, mitogen-activated protein kinases, as well as many epigenetic regulators. Special AT-rich sequence-binding protein 2 is an epigenetic regulator involved in epithelial–mesenchymal transition and osteoblastic differentiation. It has been reported that the crosstalk between several pathways is responsible for the regulation of epithelial–mesenchymal transition in cancer cells. However, crosstalks between p38 and Akt pathways involved in epithelial–mesenchymal transition are still unknown. We recently reported that there is a crosstalk between p38 and Akt pathways in non-small-cell lung carcinoma cells, and this crosstalk is associated with E-cadherin and special AT-rich sequence-binding protein 2 expressions. Therefore, we aimed to determine whether this crosstalk has a mediator role in the regulation of epithelial–mesenchymal transition in non-small-cell lung carcinoma. Our results showed that inhibition of p38 leads to the disruption of this crosstalk via decreased expression of phosphatase and tensin homolog (PTEN) and subsequently increased activation of Akt in non-small-cell lung carcinoma cells. Then, we found that p38 inhibition upregulated special AT-rich sequence-binding protein 2 expression and reversed epithelial–mesenchymal transition in non-small-cell lung carcinoma cells. Furthermore, special AT-rich sequence-binding protein 2 knockdown abolished the effect of p38 inhibition on epithelial–mesenchymal transition in non-small-cell lung carcinoma cells. In conclusion, our results strongly indicate that the crosstalk between p38 and Akt pathways can determine special AT-rich sequence-binding protein 2 expression and epithelial character of non-small-cell lung carcinoma cells, and special AT-rich sequence-binding protein 2 is a critical epigenetic regulator for epithelial–mesenchymal transition mediated by p38 pathway in non-small-cell lung carcinoma. Our findings will contribute to illuminate the molecular mechanisms of the epithelial–mesenchymal transition process that has a critical significance for lung cancer metastasis.